Michael Boyms Bericht aus Mosambik - 1644 ; Lateinischer Text, Übersetzung und Kommentar. Mit ethnographischen Paralleltexten des 16. und 17. Jahrhunderts aus der Wiener Sammlung Woldan - Robert, Wallisch (Wiener Studien Beihefte, 2005)
For several months of 1644, monsoon winds held the Pole Michael Boym, the great China missionary, in Mozambique off the coast of southeastern Africa. His report, published here for the first time, about the "Country of the Kaffirs" represents not only an important source for the local history of early modern Mozambique, but it's significance can also be seen particularly in Boym`s unusual criticism of the Portuguese colonial administration, a criticism that developed out of the basic concepts of his religious order, the Society of Jesus. Furthermore, the inner-European aspects of his disapproval of Portuguese colonialism provide interesting testimony for the fundamental changes in Western European society in the late 16th and early 17th centuries, during which the overseas empires of the Iberian discoveries were breaking down under the pressure of Northwest European powers, and the cultural hegemony of the Italo-Iberian civilisation was moving to its end.